The Effectiveness of the Kamsel Unit’s Traffic Dikmas in Reducing the Number of Traffic Accidents at Tulungagung Police - Pradana, Daffa Sava (Advances in Police Science Research Journal, 2024)
The trend in the increasing number of traffic accidents in Tulungagung Regency has implications for public security and security. To minimize the high number of traffic accidents in Tulungagung Regency, it is necessary to play the role of the South Kalimantan Unit as a unit that takes pre-emptive action by educating the public about traffic by carrying out community education activities about orderly traffic. The aim of this research is to analyze the effectiveness of the implementation of Traffic Dikmas by the Tulungagung Police South Security Unit in reducing the number of traffic accidents. The research method was carried out qualitatively through observation, interviews and document study. The theories used are Management Theory, SWOT Analysis, and Cognitive Multimedia. The results of the analysis using management theory show that there are several constraints in the South Kalimantan Unit’s resources, such as a shortage of personnel, delays in disbursement of funds, and inadequate infrastructure. On the other hand, the work system of the South Kalimantan Unit was also considered to be still ineffective because it was found that the planning was not appropriate, the organization was unclear, the implementation of Community Community Service was ineffective and there was a lack of supervision. To overcome this, it is recommended that the Tulungagung Police South Kalimantan Unit add personnel, improve internal and external coordination, apply for disbursement of funds at the start of activities, procure goods that support Traffic Dikmas activities, make a survey of the implementation of Traffic Dikmas and carry out analysis and evaluation after the activity to increase the effectiveness of the program.